Aspectos ecológicos e evolutivos da escolha dos frutos: fatores determinantes e variações individuais - Pires, Luís Paulo (2019)
Interactions between frugivores and plants are fundamental for the stability of ecological communities. Plants provide food for frugivorous animals and these disperse the seeds to suitable sites. In tropical ecosystems, birds are the most relevant seed dispersers of angiosperms, in terms of species richness. Considering the importance of this ecosystem service, this thesis aimed at: 1) discuss the coevolutionary approach of plant-frugivore interactions; 2) investigate the role of neutral and deterministic processes in assembling plant-frugivore networks; 3) assess the degree of individual specialization in a generalist bird species and 4) evaluate how environmental disturbances (i.e. edge effect) may influence color perception and fruit choice by frugivorous birds. To achieve the first goal, we did a review on the evolution of plant-frugivore interactions, focusing on the temporal congruency in the evolution and diversification patterns of frugivores and angiosperms. In this review, we agreed with authors who suggest that the selective pressures between these groups happens in pulses of coevolution, defined by periods when reciprocal evolution is strong and directional interspersed by others when coevolutionary forces are weak and diffuse. For the second objective of this study, we applied an ecological network approach and found that size constraints and temporal overlap between frugivores and resources explain pairwise interactions, but that species relative abundance performed better at explaining aggregate network metrics. In chapter 3, we once again used network theory but this time we considered the consumer nodes as different individuals in the same population. We identified that the generalist diet of the population is the sum of the niches of dietary specialist individuals and that seasonal variation in resource availability influences the dietary width of individual niche. Finally, in chapter 4 we designed an experimental study to assess if fruit color and the distance from forest borders influence fruit choice. Results showed that neither of these predictors explained fruit consumption and we believe this is due to the prevalence of opportunistic frugivorous species in the study sites. In its whole, the data and discussions presented in this thesis suggest that: 1) we need more information on the evolution of plant-frugivore interactions in order to better predict how environmental disturbances will affect species evolutionary trajectories; 2) models explaining plant-frugivore mutualistic networks should consider biological constraints and species relative abundance, but that these may not equally explain different processes of network assembling; 3) intraspecific variations in resource use are important for the establishment of biological interactions and that individual-level networks may contain properties that, albeit existent, are not evident in species-resources networks; and 4) the influence of edge effect of color-based fruit choice is mainly indirect, by modifying habitat structure and guild composition.